Optimalisasi Kepatuhan Wajib Pajak melalui Transformasi Digital dan Insentif Fiskal - Nur Aini (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
Digital transformation has become a key catalyst in the reform of tax administration in the data-driven economy era. This study aims to analyze the role of digital transformation and fiscal incentives in enhancing taxpayer compliance, with tax literacy serving as a significant reinforcing variable. A quantitative approach was employed using primary data collected through questionnaires distributed to active taxpayers in Indonesia. Multiple linear regression analysis was applied to examine the relationship between digital transformation, fiscal incentives, tax literacy, and taxpayer compliance. The findings reveal that digital transformation has a positive and significant impact on improving taxpayer compliance by enhancing efficiency and transparency within the tax administration system. Fiscal incentives were also found to be effective in encouraging compliance motivation, particularly when integrated with digital systems that simplify tax reporting and payment processes. Moreover, tax literacy plays a strong mediating role, amplifying the effects of digital transformation and fiscal incentives on compliance behavior. These results confirm that successful tax reform in the digital era depends not only on technological infrastructure but also on improving taxpayers’ awareness and understanding of fiscal responsibility. This study provides both theoretical and practical contributions to the development of adaptive, transparent, and sustainable national fiscal policies. It recommends that the government strengthen the integration of the national digital tax system, develop data-based tax literacy programs, and refine fiscal incentive designs to more effectively promote long-term taxpayer compliance.